2020
DOI: 10.26442/00403660.2020.04.000590
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of mechanical bacterial lysate in the prevention of infectious exacerbations of chronic obstructive pulmonary disease

Abstract: Aim. To evaluate the efficacy of mechanical bacterial lysate on the prevention of infectious exacerbations of chronic obstructive pulmonary disease in patients with frequent exacerbations. Materials and methods. The study included patients (n=60) with frequent exacerbations of COPD (groups C and D according to the GOLD classification). All COPD patients were divided into two groups by blind method. The first group (n=30) received conventional therapy for COPD plus MBL (the course included 3 cycles of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Administration of bacteria-based immunomodulatory agents induces polarization of immune response, mainly type Th1, and is associated with an increase in NK cytotoxicity and an enhanced expression of TLR2, TLR4, and TLR9 [9]. So far, a large number of papers have been published focusing on the use of bacteria-based vaccines in the treatment of obstructive pulmonary disease and asthma [10,11,12,13]. The results of the studies investigating the e cacy of immunomodulatory agents in COVID-19 infection are, however, scarce, anecdotal, and sometimes not evidence-based.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of bacteria-based immunomodulatory agents induces polarization of immune response, mainly type Th1, and is associated with an increase in NK cytotoxicity and an enhanced expression of TLR2, TLR4, and TLR9 [9]. So far, a large number of papers have been published focusing on the use of bacteria-based vaccines in the treatment of obstructive pulmonary disease and asthma [10,11,12,13]. The results of the studies investigating the e cacy of immunomodulatory agents in COVID-19 infection are, however, scarce, anecdotal, and sometimes not evidence-based.…”
Section: Introductionmentioning
confidence: 99%
“…На сегодняшний день опубликовано достаточное количество работ по применению бактериальных вакцин в лечении хронической обструктивной болезни легких и бронхиальной астмы [1,7,9,11]. Однако исследования эффективности применения иммуномодуляторов при ВП разрозненны и не всегда доказательны.…”
unclassified
“…During the process, we found that the study by Ricci et al ( 13 ) was ancillary to the AIACE study ( 2 ), but retained it because it reported complementary data. Ultimately, this meta-analysis included 12 studies, namely, nine randomized controlled trials and three abstracts of randomized controlled trials with sufficient data ( 8 10 , 13 – 21 ). Figure 1 summarizes the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…First, we conducted a subgroup analysis. The forest and radial plots ( Figure 7 ) analyzing the effect on the exacerbation rate showed obvious heterogeneity for mechanical bacterial lysates; Avdeev et al ( 8 ) included patients with a lower FEV 1 /predicted and found a higher RR, and might be the source of heterogeneity. After removing this study, the heterogeneity decreased (overall: RR = 0.88, 95% CI 0.79–0.97, P = 0.009; heterogeneity: P = 0.24, I 2 = 25%; mechanical bacterial lysate subgroup: RR = 0.92, 95% CI 0.71–1.21, P = 0.57; heterogeneity: P = 0.42, I 2 = 0).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation